Biculturalism Badui people's identity: a case study on Seba Badui 2023 - R. Nia Kania Kurniawati; Liza Diniarizky Putri; Ichsan Adil Prayogi; Dian Wardiana Sjuchro; Ramon K. Santos III (Faculty of Communications Science, Dr. Soetomo University, 2023)
This research discusses how an indigenous community assimilates two divergent cultures in the wake of Globalisation, specifically focusing on the influence of technology. The subject of this study is the Baduis people of Banten. Drawing upon McLuhan's media ecology theory, this qualitative research adopts a case study approach. The research centres on the Badui people, focusing on the Baduy Seba activities that transpired in April 2023. The primary aim is to examine how this Indigenous society, which initially resisted technology, eventually engages in the process of cultural acculturation. The findings of this study reveal that the Banten Baduis people demonstrate a reserved demeanour in the face of Globalisation's influence, choosing to embrace change cautiously while still preserving their core values. This cautious and adaptive attitude of the Baduis people towards the swift influence of technology reflects their biculturalism, where they successfully blend their traditional customs with aspects of the modern world.